Implementasi Pendekatan Gamifikasi dalam Pembelajaran Fisika: Analisis Bibliometrik - Astuti, Irnin Agustina Dwi; Bhakti, Yoga Budi; Okyranida, Indica Yona; Prasetya, Rendi (UNIVERSITAS INDRAPRASTA PGRI, 2024)
To enhance problem-solving skills in physics education, a learning model strategy is needed that can effectively visualize physics concepts and promote interactive learning. One of the learning approaches that can be utilized is gamification. This study aims to analyze the implementation of gamification in physics education using a bibliometric approach with the VOSViewer software. The method used in this study is bibliometric analysis. There are 5 classification clusters identified through the VOSViewer software. The results of the study show that articles using the keywords